Revolution and Terror, or how Louis XVI was turned into a pig - Rogozinski, Jacob (Stasis, 2014)
In this paper, we will analyze the relationship between Revolution and Terror by focusing on the example of the Jacobin Terror in 1793. After reviewing the classical interpretations of Hannah Arendt and C. Lefort, the problem of Terror is approached from a phenomenological analysis of the Body Politic, its incarnation in the body of the monarch and the threat of its disincorporation. We are particularly interested in the designation of the King and Queen as absolute enemies, through caricatures that represent them as dangerous or vile animals. Using Michelet and Quinet’s critique of the “Jacobin Inquisition,” the ambivalent meaning of regicide is finally understood as transfer of sovereignty and matrix of Terror.